PERM1 regulates energy metabolism in the heart via ERRα/PGC−1α axis - Oka, Shin-ichi; Sreedevi, Karthi; Shankar, Thirupura S.; Yedla, Shreya; Arowa, Sumaita; James, Amina; Stone, Kathryn G.; Olmos, Katia; Sabry, Amira D.; Horiuchi, Amanda; Cawley, Keiko M.; O’very, Sean A.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims PERM1 is a striated muscle-specific regulator of mitochondrial bioenergetics. We previously demonstrated that PERM1 is downregulated in the failing heart and that PERM1 positively regulates metabolic genes known as targets of the transcription factor ERRα and its coactivator PGC-1α in cultured cardiomyocytes. The aims of this study were to determine the effect of loss of PERM1 on cardiac function and energetics using newly generated Perm1-knockout (Perm1–/–) mice and to investigate the molecular mechanisms of its transcriptional control. Methods and results Echocardiography showed that ejection fraction and fractional shortening were lower in Perm1–/– mice than in wild-type mice (both p < 0.05), and the phosphocreatine-to-ATP ratio was decreased in Perm1–/– hearts (p < 0.05), indicating reduced contractile function and energy reserves of the heart. Integrated proteomic and metabolomic analyses revealed downregulation of oxidative phosphorylation and upregulation of glycolysis and polyol pathways in Perm1–/– hearts. To examine whether PERM1 regulates energy metabolism through ERRα, we performed co-immunoprecipitation assays, which showed that PERM1 bound to ERRα in cardiomyocytes and the mouse heart. DNA binding and reporter gene assays showed that PERM1 was localized to and activated the ERR target promoters partially through ERRα. Mass spectrometry-based screening in cardiomyocytes identified BAG6 and KANK2 as potential PERM1’s binding partners in transcriptional regulation. Mammalian one-hybrid assay, in which PERM1 was fused to Gal4 DNA binding domain, showed that the recruitment of PERM1 to a gene promoter was sufficient to activate transcription, which was blunted by silencing of either PGC-1α, BAG6, or KANK2. Conclusion This study demonstrates that PERM1 is an essential regulator of cardiac energetics and function and that PERM1 is a novel transcriptional coactivator in the ERRα/PGC-1α axis that functionally interacts with BAG6 and KANK2.